Broadband antireflective and superhydrophobic coatings for solar cells. (June 2019) - Li, Wei; Tan, Xinyu; Zhu, Jinlin; Xiang, Peng; Xiao, Ting; Tian, Lihong; Yang, Aibi; Wang, Man; Chen, Xiaobo
Abstract: High-performance, broadband antireflective (AR) and superhydrophobic coatings are fabricated on glass through deposition of silica nanoparticles with spin coating method, followed by calcination and hydrophobic modification. Silica particles with unique porous structures not only increase the roughness of the coating, but also enhance the transmittance of the glass. The coated glass has displayed a large transmittance of 99% at wavelength of 580 nm, an absolute transmittance increase by 6% or more in the wavelength range of 480–900 nm, and an excellent hydrophobicity with a water contact angle (WCA) of 147° and a sliding angle < 10°. As a result, this coating effectively improves the short-circuit current density from 13.27 to 14.17 mA/cm 2 and the conversion efficiency from 6.03 to 6.64% for dye-sensitized solar cells (DSSCs), with a 10.12% improvement. This work thus has shown a promising approach to enhance the performance of solar cells with broadband antireflective coating surfaces. Graphical abstract: A porous antireflective and superhydrophobic coating increases the performance of quasi-solid-state dye-sensitized cells with self-cleaning functions.Image 1 Highlights: The coating has a maximum transmittance of 99% near 580 nm. An absolute transmittance increase by 5% or more in the wavelength range of 430–900 nm. The coating exhibits a water contact angle of 146° and a sliding angle <10°. The cell with the coating shows 10.12% performance improvement than that without. The coated surface possesses good self-cleaning performance.